2015
DOI: 10.4155/fmc.15.133
|View full text |Cite
|
Sign up to set email alerts
|

Getting It Right: 3D Cell Cultures for the Assessment of Photosensitizers for Photodynamic Therapy

Abstract: Core quote "Cancer drug screening is rapidly moving towards the use of 3D cell models. The added complexity of PDT action makes this a conditio sine qua non for the screening of new photosensitizers."The quest for the treatment of malignant diseases is ongoing. Classic modalities based on chemo-and radiotherapy and surgery are now supplanted by or used in conjunction with photodynamic therapy (PDT) [1]. PDT involves on the administration of a photosensitizing dye and its accumulation in the affected tissue. Af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…For example, the part of PDT effect that can be related to indirect vascular and immunological mechanisms is not considered. 45 Using immunofluorescence labeling, we found that PDTinduced oxygen depletion might contribute to proliferation restriction and induction of apoptosis of hypoxic cells in the center of the spheroid. Functional tumors are interspersed with blood and lymphatic vessels, which do not allow this observation to be entirely translated to the human body.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…For example, the part of PDT effect that can be related to indirect vascular and immunological mechanisms is not considered. 45 Using immunofluorescence labeling, we found that PDTinduced oxygen depletion might contribute to proliferation restriction and induction of apoptosis of hypoxic cells in the center of the spheroid. Functional tumors are interspersed with blood and lymphatic vessels, which do not allow this observation to be entirely translated to the human body.…”
Section: Discussionmentioning
confidence: 90%
“…Compared to the situation in vivo, this basic spheroid model still has some limitations. For example, the part of PDT effect that can be related to indirect vascular and immunological mechanisms is not considered 45 . Using immunofluorescence labeling, we found that PDT‐induced oxygen depletion might contribute to proliferation restriction and induction of apoptosis of hypoxic cells in the center of the spheroid.…”
Section: Discussionmentioning
confidence: 99%
“…This trend has been introduced also in research related to photodynamic therapy (PDT) (Ref. , other references in this review). This anticancer treatment modality combines selective accumulation of a photosensitizing agent within tumor tissue with subsequent activation of the photosensitizing agent by suitable visible light.…”
Section: Introductionmentioning
confidence: 93%
“…This novel heterodimer complex (compound 3 ), presented in Figure 2c, exhibiting improved fluorescence behavior, based on a non-fluorescent Fe-metalloporphyrin with already proven electrical O 2 sensing capacities [34,35,36,37,38,39,40] and a highly fluorescent phosphor-porphyrin derivative is expected to act as conjugated chemosensor system for O 2 . These properties may also lead to potential future applications in biological fields, for example, as a bio-degradable 1 O 2 -sensitizer [34] and to show photodynamic therapy of cancer (PDT) and bactericidal activity under visible-light irradiation [36,37,38,39].…”
Section: Introductionmentioning
confidence: 99%
“…These properties may also lead to potential future applications in biological fields, for example, as a bio-degradable 1 O 2 -sensitizer [34] and to show photodynamic therapy of cancer (PDT) and bactericidal activity under visible-light irradiation [36,37,38,39]. …”
Section: Introductionmentioning
confidence: 99%